Resistensi Yoga dalam Meningkatkan Konsentrasi Ketepatan Memanah - Arisman Arisman; Ardo Okilanda; Dede Dwiansyah Putra; Muhsana El Cintami Lanos (Jurnal Patriot, 2021)
This study aims to determine the effect of yoga practice on the accuracy of concentration in archery in athletes of UKM Panahan Umika Bekasi. This yoga practice has a great impact both in terms of individual character and in terms of health. The population of this study was 28 people consisting of boys and girls, while the sample consisted of 18 male athletes with a sampling technique, namely positive sampling. The results of this study show the effect of yoga practice on archery accuracy. These results were obtained based on the t-test with details (tcount 4.94> ttable 1.74).